Effects of forest fires in the wood of Prosopis alba Griseb. y Prosopis nigra (Griseb.) Hieron, Mimosaceae - Bravo, Sandra; Giménez, Ana María; Moglia, Juana Graciela (Bosque (Valdivia), 2001)
Fire effects on Prosopis alba and P. nigra growing in Dry Chaco (Argentina) at two sites (Sachayoj and Coronel Rico, Santiago del Estero Province) were evaluated. Different types of damage were identified and classified in terms of scars and fire marks. Scar lesions were the most frequent and severe, and caused defects in the shafts, such as ribs, shakes, checks, inner bark damage and discolored wood. The most frequent percentage of cambial ring loss or alteration was between 1% and 20%. The highest frequency of lesions was recorded up to 2.30 m in height, which represents the technological profitable part of the shafts. Discolored wood was restricted to wood growing before wounding, with heavy deposits in the vessels, fibers and ray cells. Changes in the basic pattern of tissues were recorded in the wood formed after wounding, such as the increment of axial and radial parenchyma. A reduction of fibers and vessels and disorientation of the axial cells was also detected. All of these alterations reduce the commercial stem volume and wood quality in P. alba and P. nigra.